Pip serves as an intermediate in RpoS-modulated phz2 expression and pyocyanin production in Pseudomonas aeruginosa. (October 2020) - Chen, Lijuan; Xu, Xinyu; Fan, Chen; Zhang, Rui; Ji, Yingyu; Yu, Zhifen; Qu, Huige; Feng, Zhibin; Chi, Xiaoyan; Cheng, Shiwei; Ge, Yihe
Abstract: Pyocyanin, a main virulence factor that is produced by Pseudomonas aeruginosa, plays an important role in pathogen-host interaction during infection. Two copies of phenazine-biosynthetic operons on genome, phz1 ( phzA1B1C1D1E1F1G1 ) and phz2 ( phzA2B2C2D2E2F2G2 ), contribute to phenazine biosynthesis. In our previous study, we found that RpoS positively regulates expression of the phz2 operon and pyocyanin biosynthesis in P. aeruginosa PAO1. In this work, when a TetR-family regulator gene, pip, was knocked out, we found that pyocyanin production was dramatically reduced, indicating that Pip positively regulates pyocyanin biosynthesis. With further phenazines quantification and β-galactosidase assay, we confirmed that Pip positively regulates phz2 expression, but does not regulate phz1 expression. In addition, while the rpoS gene was deleted, expression of pip was down-regulated. Expression of rpoS in the wild-type PAO1 strain, however, was similar to that in the Pip-deficient mutant PAΔ pip, suggesting that expression of pip could positively be regulated by RpoS, whereas rpoS could not be regulated by Pip. Taken together, we drew a conclusion that Pip might serve as an intermediate in RpoS-modulated expression of the phz2 operon and pyocyanin biosynthesis in P. aeruginosa . Highlights: Deletion of pip causes decreased pyocyanin biosynthesis in P. aeruginosa . Not phz1 but phz2 was down-regulated in the absence of Pip. Pip acts as an intermediate in RpoS-mediated regulation of the phz2 expression.